Decade Long Trends (2001–2011) in Duration of Pre‐Hospital Delay Among Elderly Patients Hospitalized for an Acute Myocardial Infarction. Issue 4 (April 2016) - Makam, Raghavendra P.; Erskine, Nathaniel; Yarzebski, Jorge; Lessard, Darleen; Lau, Jason; Allison, Jeroan; Gore, Joel M.; Gurwitz, Jerry; McManus, David D.; Goldberg, Robert J.
Abstract : Background: Early intervention with medical and/or coronary revascularization treatment approaches remains the cornerstone of the management of patients hospitalized with acute myocardial infarction (AMI). However, several patient groups, especially the elderly, are known to delay seeking prompt medical care after onset of AMI‐associated symptoms. Current trends, and factors associated with prolonged prehospital delay among elderly patients hospitalized with AMI, are incompletely understood. Methods and Results: Data from a population‐based study of patients hospitalized at all 11 medical centers in central Massachusetts with a confirmed AMI on a biennial basis between 2001 and 2011 were analyzed. Information about duration of prehospital delay after onset of acute coronary symptoms was abstracted from hospital medical records. In patients 65 years and older, the overall median duration of prehospital delay was 2.0 hours, with corresponding median delays of 2.0, 2.1, and 2.0 hours in those aged 65 to 74 years, 75 to 84 years, and in patients 85 years and older, respectively. There were no significant changes over time in median delay times in each of the age strata examined in both crude and multivariable adjusted analyses. A limited number of patient characteristics were associated with prolonged delay in this patient population. Conclusions: The results of this community‐wide study demonstrate that delay in seeking prompt medical care continues to be a significant problem among elderly patients hospitalized with AMI. The lack of improvement in the timeliness of patients' care‐seeking behavior during the years under study remains of considerable clinical and public health concern.